Perfil higiênico - sanitário e tecnológico de açougues no município de Ribeirão Preto (SP) - 2001 - Flavia Fulukava do Prado (2002)
The present work aimed to describe and to discuss on the hygienic - sanitary profile of butcher shops in the city of Ribeirão Preto (SP) during the year of 2001. Of a sampling universe of 336 butcher shops registered in the city registry, 95 were randomly selected for the study. The hygienical - sanitary profile of these shops was evaluated, characterizing them regarding to the administrative region, built area, period of activity, number of employees and education level of the mananger. The parameters considered were as established by Resolição SS-196, published on December 29, 1998 by state of São Paulo which takes into consideration five main aspects: 1) building structure and maintenance; 2) equipamenr and kitchenware; 3) workr's personal hyygiene and care; 4) raw materials and final products; 5) production flow and quality control. The majority (60,4%) of the places have less than five years in the activity, probably justified by t he economic change in Brazil in this period and the high rate of population growth in this city. The general classification of the establishments was: very bad 14%, bad 70%, good 15% and very good 1%. No relation of educational level with classification of the establishments was detected. The high percentage of very bad an bad establishments was a consequence of hygienical imperfections, due to inadequate handing of the products as well as some structural imperfections according to the legislation. In the comparison among the different administrative regions, the South region presented certain suoeriority in some characteristics due to a better clientele with higher purchasing power and privileged localization, forcing the implementation of a retail trade with better quality in the instalation of this service. Meat temperatures were all superior to proposed by the technical-scientific studies and the current legislation therefore being inadequate. A difficulty in establishing the ideal principles of quality was noted, due to abscence of clarity of the legislation and lack of adequate personnel training.